Evaluation of endometrial thickness in breast cancer patients with tamoxifen treatment - Difference between 2-dimensional ultrasonography and elastosonography - Hyun Been Jo; Hyun Joo Lee; Seung Chul Kim; Jong Kil Joo; Dong Soo Suh; Ki Hyung Kim (Elsevier, 2023)
Objective: This study aimed to confirm the clinical significance of elastographic endometrium measurement in comparison with conventional ultrasonography for tamoxifen users with breast cancer. Materials and methods: In this retrospective analysis, 98 women receiving tamoxifen as postoperative breast cancer treatment were included. Patient medical charts were reviewed, and related medical, obstetric, and gynecological information and histories relevant to breast cancer were evaluated. Patient clinical imaging data included endometrial thickness measurements using both conventional ultrasonography and elastography, and the differences between these two modalities in delta values were statistically analyzed along with possible influencing factors. Results: Endometrial thickness measured using 2-dimensional ultrasonography had a mean value of 5.81 mm (standard deviation [SD] = 3.09), and elastosonography showed a mean value of 3.07 mm (SD = 1.62). A paired t-test was conducted and a significant difference between them was confirmed (P-value <0.001). Logistic regression analysis revealed that age and duration of tamoxifen treatment significantly influenced the degree of difference between endometrial thickness measurements. Conclusions: Elastosonography may be a more successful and useful tool for measuring actual endometrial thickness than generalized 2-dimensional ultrasonography. In clinical cases with limited use of elastosonography and consequent inability for thorough evaluation of endometrial thickness, practitioners should exercise caution in deciding whether or not to adopt invasive diagnostic procedures, such as endometrial curettage, especially for young patients of reproductive age or those with prolonged treatment of breast cancer with tamoxifen.